ANALISIS SOAL HOTS PADA BUKU SISWA TOKOH PENJELAJAH ANGKASA LUAR - Wasifatun Najiroh; Muhammad Agung Rokhimawan (Profesi Pendidikan Dasar, 2020)
This study aims to describe the evaluation questions, find out the form of the questions and show HOTS questions in the Thematic book with indicators analyzing (C4), evaluating (C5) and creating (C6) the questions in the thematic books. This study includes a qualitative approach with the subject of evaluation questions on the Thematic student book subtheme character explorer space. Content content analysis is an analysis technique used in research. The results of the analysis of HOTS questions on the book class VI students of the space explorer sub-theme that there are 120 items with 63 items are questions with the cognitive realm of higher order thinking or Higher Order Thinking Skills (HOTS). 57 items are questions with the cognitive realm of low thinking or Lower Order Thinking Skills (LOTS).